Comparative Study of Nasionalism Main Characters in The Novel Negeri van Oranje and Diary Buruh Migran - Purwati Anggraini; Galuh Farah Rahma Yunita (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2020)
Negeri van Oranje by Wahyuningtyas and Diary Buruh Migran by Arsya Kirana is a literature work that shows the main character’s struggle in a foreign country. Based on both novel, this research is aim for (1) describing the nationalism of the main character on novel titled Negeri Van Oranje by Wahyuningtyas and novel titled Diary Buruh Migran by Arsya Kirana, and also (2) describing the impact of the character of nationalism on other figures inside novel titled Negeri Van Oranje by Wahyuningtyas and novel titled Diary Buruh Migran by Arsya Kirana. This research using descriptive approach with qualitative type. Analysis result shows there is an existence five sub values of national characterism, pervade social care, hard work, high curiosity, care for living, and loves the motherland. One of them is care for living not founded on novel titled Diary Buruh Migran by Arsya Kirana, that’s create a primacy for novel titled Negeri van Oranje by Wahyuningtyas. Overall, character of nationalism has an impact on other characters in the story, which involve cognitive components, affective components, and conative components.